Teología y Vida. Antecedentes de origen - Arenas, Sandra (Teología y vida, 2019)
Through previously unexplored archival material, the article rebuilds the foundational antecedents of the theological Chilean Journal Teología y Vida. Its origins are situated within a general program of ecclesial and institutional-academic renewal which Marcos McGrath, its mentor and first director, pushed forward in line with the intellectual and ecclesial ambiance of transformations in the 60'. This survey brings up the issue of the role of theology in society, academy and the church.